If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 3 + -10 = 3(3x + 3) Reorder the terms: 3 + -10 + 9x = 3(3x + 3) Combine like terms: 3 + -10 = -7 -7 + 9x = 3(3x + 3) Reorder the terms: -7 + 9x = 3(3 + 3x) -7 + 9x = (3 * 3 + 3x * 3) -7 + 9x = (9 + 9x) Add '-9x' to each side of the equation. -7 + 9x + -9x = 9 + 9x + -9x Combine like terms: 9x + -9x = 0 -7 + 0 = 9 + 9x + -9x -7 = 9 + 9x + -9x Combine like terms: 9x + -9x = 0 -7 = 9 + 0 -7 = 9 Solving -7 = 9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -2(b+3)=15 | | -8x-55=2x+75 | | 8x-2=-9+1x | | 4(3m+1)=8m+20 | | 5-(3x+9)-2x=15x-2(x-5) | | 3n+7=-2n+17 | | .6x+3=27 | | m/4-8=10 | | 2x-7+4x+1=12 | | Y=4.5x+12 | | [4x+42]=[24+6y] | | 0.9(220-a)=178.2 | | 5w+1=0 | | 2-7p-2=2p+9 | | X+3x+2x=x | | 13x+4x+3+6=10+27+3x | | 11-c=7 | | y+7=.33(x+2) | | 3(m+4)=7m-8 | | 2.25*1.8= | | -34-7x=-4x+44 | | b=c-r | | 14+8f-5(2f-3)= | | -34-7x=4x+44 | | y+7=.333(x+2) | | 2x+4+2x+9+x-3=180 | | 4x^2-80x+224=0 | | 6c-8=34 | | 2sin(x)-4cos(x)-2=0 | | -6x-8+3x=3-3x+28 | | 76=(2x+4) | | 6x=4(x-9) |